Scratching increases epidermal neuronal branching and alters psychophysical testing responses in atopic dermatitis and brachioradial pruritus - Renkhold, Lina; Wiegmann, Henning; Pfleiderer, Bettina; Süer, Aysenur; Zeidler, Claudia; Pereira, Manuel P.; Schmelz, Martin; Ständer, Sonja; Agelopoulos, Konstantin (Frontiers in Molecular Neuroscience, 2023)
Background: Chronic scratching imposes a major stress on the skin and can lead to itch intensity worsening and consequently patients may enter an itch-scratch cycle. This repetitive mechanical stress can result in lichenification with worsening of epidermal barrier function and enhanced cutaneous inflammation. Further, a reduction of intraepidermal nerve fibers was previously described in lichenifications.The aim of this study was to investigate the influence of chronic scratching on the epidermal neuroanatomy as well as on sensory changes in particular the prevalence of hyperknesis and alloknesis of the patients after mechanical, chemical, and electrical stimuli.Methods: Analyses were performed in pruritic lichenified (chronically scratched), pruritic nonlichenified (not chronically scratched) and non-pruritic non-lesional (not affected) skin areas of patients with inflammatory pruritus, i.e. atopic dermatitis (n=35) and neuropathic pruritus, i.e. brachioradial pruritus (n=34) vs. healthy matched controls (n=64). Our fine-grained spatial skin characterization enabled specifically studying differential effects of chronic scratching in inflammatory and neuropathic itch.Results: Analysis of intraepidermal nerve fiber density showed rarefaction of fibers in all three skin areas of patients compared with healthy controls in both diagnoses. Even more, the two pruritic areas had significantly less nerve fibers than the not affected skin whereas electrically induced itch was massively increased. Epidermal branching of the remaining nerve fibers in lichenified / chronically scratched skin was increased particularly in patients with brachioradial pruritus which may contribute to the pronounced local neuronal sensitivity. Hyperknesis and alloknesis were found increased independent of lichenification.Our results indicate that chronic scratching may not affect intraepidermal nerve fiber density but leads to a stronger branching pattern of intraepidermal nerve fibers which may contribute to local hypersensitivity. The increased sensitivity in the pruritic areas suggests mechanisms of peripheral sensitization, whereas the increased sensation on electrically and 64 chemically induced itch in not affected skin indicates central sensitization for itch.